(untitled) (Педагогіка вищої та середньої школи, 2007)
In article is analyzed essence of the notion "competence” and features competency in domestic and foreign pedagogical science and practice. The author considers specific groups of the personality-oriented education which caused it as factor of the shaping one of the key competency - a skills to learn. Also the author offers a facility of the education, influencing upon shaping the intellectual sphere of personality.